A Model in Conflict Prevention in The Era of Information Technology to Maintain Zero Conflict in South Sumatra - Suhardi, Agus; Sobri, Kiagus Muhammad; Sriati, Sriati; Najib, Abdul (Eduvest - Journal of Universal Studies, 2025)
Technological developments provide convenience in daily activities and cause negative impacts, such as social conflicts. In South Sumatra Province, this problem has the potential to threaten the achievement of Zero Conflict that has been achieved. This study aims to analyze the government's strategy in preventing conflicts with technoculture-based information technology. The theories used include Conflict Theory as a grand theory, New Public Administration Theory as a middle theory, conflict prevention strategies, and digital technology interaction in creating conflicts as a theoretical application. A qualitative approach is applied to analyze written material from various sources. The findings show that the potential for disruption to Zero Conflict is quite significant. The South Sumatra government has made preventive efforts through three strategies: early warning and system response, confidence-building actions, and diplomatic missions. To maintain Zero Conflict, it is necessary to search, study, and diagnose to detect the negative impact of technoculture-based conflicts to maintain harmony and balance between information technology and culture.